Distribution of the rDNA and three classes of highly repetitive DNA in the chromatin of interphase nuclei of Arabidopsis thaliana - Bauwens, S; Van Oostveldt, P; Engler, G; Van Montagu, M (Chromosoma, 1991)
The distribution of the ribosomal RNA (rRNA) genes and three classes of highly repetitive DNA in the chromatin of interphase nuclei of Arabidopsis thaliana was studied for the first time through non-isotopic in situ hybridization and luminescence digital imaging microscopy. Each of the three classes of highly repetitive DNA exhibited a characteristic hybridization pattern, and one class was seen to be primarily localized on two chromocentres, which would allow it to distinguish a particular chromosome. The rDNA was consistently localized on the two largest chromocentres and on one or two smaller chromocentres. A limited number of nuclei exhibited more than four labelled chromocentres, indicative of either polypoidy or differential amplification of the rDNA. In nuclei where the nucleolus could be clearly observed, the nucleolar associated chromocentres (NACs) were seen to be labelled by the ribosomal DNA (rDNA) probe.